Fulfillment of The Children's Needs: Cultural Economic Actors and Capital in Building Welfare of Life - Evi Melda; Subaidi Subaidi (LPPM IAIN Parepare, 2022)
Children are one of the nation’s development assets that is believed to change the level of welfare of people’s lives. Therefore, the fulfillment of children’s rights is part of human rights that must be guaranteed and fulfilled by parents, society, and the state. Fulfillment of children’s need is important because it can affect the growth and development of children. The main problem in this study is how to fulfill the rights of children by parents? The aim is to describe the efforts made by parents in fulfilling the rights of children who work in sand mining. This type of research is classified as qualitative, with a sociological research approach. The theory used is functional structural theory. This theory interprets society as a structure with parts that are always related and influence each other. The data collection methods used were observation, interviews, and documentation. The results showed that there were four efforts made by parents in fulfilling children’s rights, namely: fulfillment of the right to life, fulfillment of growth and development rights, fulfillment of protection rights, and fulfillment of children’s participation rights. So that with these efforts, some children can carry out their basic rights.